ANALISIS YURIDIS PERTIMBANGAN HUKUM PENGADILAN AGAMA TENTANG PEMBATALAN HIBAH (STUDI PUTUSAN NOMOR 498/Pdt.G/2019/PA.Blcn) - NIM. A1011201162, NAZLA LATIFAH (Fakultas Hukum Universitas Tanjungpura, 2024)
ABSTRACT A gift is a gift from someone to another person where the giver is still alive. As for Islamic Law, there is no maximum amount of a person's assets that can be donated, and the implementation of the gift can be done in writing or verbally. Islamic law regulates that a gift cannot be canceled or revoked because it is a gift that has been received by the gift giver, however there are exceptions when the gift is given by parents to their children, this is also accommodated in Article 212 of the Compilation of Islamic Law that the gift cannot be withdrawn. except for gifts from parents to children. This research aims to find out and analyze the basis of the Judge's legal considerations regarding the cancellation of grants regarding decision Number 498/Pdt.G/2019/PA.Blcn. and To find out the impact of the judge's legal considerations on the parties regarding the cancellation of the grant. In this research, normative research methods are used, this type of research approach uses a statutory approach (Statute Approach) and case approach (Case Approach). In this research, the theory used is the theory of legal objectives. The theory used in this research is the theory of legal objectives. Gustav Radbruch said that there are three objectives of law, namely benefit, certainty and justice. In its deliberations, the Judicial Council weighed in with the provisions of Article 212 of the KHI, which states that grants cannot be withdrawn, except for grants from parents to their children. And the Council of Judges is of the opinion that revocation should be understood by both parents, namely the father and mother, as well as by one of them in canceling the grant either with or without the consent of the parties in accordance with the legal opinion in Kitab Majmu' Syarah Al Muhazzab, Volume 6, Beirut: Dar Al Fikr, Page 276